Own and sibling effects of conditional cash transfer programs : theory and evidence from Cambodia - Ferreira, Francisco H.G.; Filmer, Deon; Schady, Norbert (2012)
Conditional cash transfers have been adopted by a large number of countries in the past decade. Although the impacts of these programs have been studied extensively, understanding of the economic mechanisms through which cash and conditions affect household decisions remains incomplete. This paper uses evidence from a program in Cambodia, where eligibility varied substantially among siblings in the same household, to illustrate these effects. A model of schooling decisions highlights three different effects of a child-specific conditional cash transfer: an income effect, a substitution effect, and a displacement effect. The model predicts that such a conditional cash transfer will increase enrollment for eligible children - due to all three effects - but have an ambiguous effect on ineligible siblings. The ambiguity arises from the interaction of a positive income effect with a negative displacement effect. These predictions are shown to be consistent with evidence from Cambodia, where the child-specific program makes modest transfers, conditional on school enrollment for children of middle-school age. Scholarship recipients were more than 20 percentage points more likely to be enrolled in school and 10 percentage points less likely to work for pay. However, the school enrollment and work of ineligible siblings was largely unaffected by the program.